Patient relevant outcomes of unicompartmental versus total knee replacement: systematic review and meta-analysis. (21st February 2019) - Wilson, Hannah A; Middleton, Rob; Abram, Simon G F; Smith, Stephanie; Alvand, Abtin; Jackson, William F; Bottomley, Nicholas; Hopewell, Sally; Price, Andrew J
Abstract: Objective: To present a clear and comprehensive summary of the published data on unicompartmental knee replacement (UKA) or total knee replacement (TKA), comparing domains of outcome that have been shown to be important to patients and clinicians to allow informed decision making. Design: Systematic review using data from randomised controlled trials, nationwide databases or joint registries, and large cohort studies. Data sources: Medline, Embase, Cochrane Controlled Register of Trials (CENTRAL), and Clinical Trials.gov, searched between 1 January 1997 and 31 December 2018. Eligibility criteria for selecting studies: Studies published in the past 20 years, comparing outcomes of primary UKA with TKA in adult patients. Studies were excluded if they involved fewer than 50 participants, or if translation into English was not available. Results: 60 eligible studies were separated into three methodological groups: seven publications from six randomised controlled trials, 17 national joint registries and national database studies, and 36 cohort studies. Results for each domain of outcome varied depending on the level of data, and findings were not always significant. Analysis of the three groups of studies showed significantly shorter hospital stays after UKA than after TKA (−1.20 days (95% confidence interval −1.67 to −0.73), −1.43 (−1.53 to −1.33), and −1.73 (−2.30 to −1.16), respectively). There was no significant difference in pain, based on patient reported outcome measures (PROMs), but significantly better functional PROM scores for UKA than for TKA in both non-trial groups (standard mean difference −0.58 (−0.88 to −0.27) and −0.29 (−0.46 to −0.11), respectively). Regarding major complications, trials and cohort studies had non-significant results, but mortality after TKA was significantly higher in registry and large database studies (risk ratio 0.27 (0.16 to 0.45)), as were venous thromboembolic events (0.39 (0.27 to 0.57)) and major cardiac events (0.22 (0.06 to 0.86)). Early reoperation for any reason was higher after TKA than after UKA, but revision rates at five years remained higher for UKA in all three study groups (risk ratio 5.95 (1.29 to 27.59), 2.50 (1.77 to 3.54), and 3.13 (1.89 to 5.17), respectively). Conclusions: TKA and UKA are both viable options for the treatment of isolated unicompartmental osteoarthritis. By directly comparing the two treatments, this study demonstrates better results for UKA in several outcome domains. However, the risk of revision surgery was lower for TKA. This information should be available to patients as part of the shared decision making process in choosing treatment options. Systematic review registration: PROSPERO number CRD42018089972.